The Sacrality of Frederick II of Swabia - Vagnoni, Mirko (De Medio Aevo, 2012)
By following the Kaiser Friedrich II of Ernst Kantorowicz, historians have often talked about the divine and messianic, as well as the angelic and priestly character of Frederick II (1194-1250). This paper presents the results of the analysis both of iconographic and written sources produced in the Swabian court, by calling into question the traditional interpretation.